Human myogenic reserve cells are quiescent stem cells that contribute to muscle regeneration after intramuscular transplantation in immunodeficient mice - Thomas Laumonier (Nature Portfolio, 2017)
Abstract Satellite cells, localized within muscles in vivo, are Pax7+ muscle stem cells supporting skeletal muscle growth and regeneration. Unfortunately, their amplification in vitro, required for their therapeutic use, is associated with reduced regenerative potential. In the present study, we investigated if human myogenic reserve cells (MRC) obtained in vitro, represented a reliable cell source for muscle repair. For this purpose, primary human myoblasts were freshly isolated and expanded. After 2 days of differentiation, 62 ± 2.9% of the nuclei were localized in myotubes and 38 ± 2.9% in the mononucleated non-fusing MRC. Eighty percent of freshly isolated human MRC expressed a phenotype similar to human quiescent satellite cells (CD56+/Pax7+/MyoD−/Ki67− cells). Fourteen days and 21 days after cell transplantation in immunodeficient mice, live human cells were significantly more numerous and the percentage of Pax7+/human lamin A/C+ cells was 2 fold higher in muscles of animals injected with MRC compared to those injected with human myoblasts, despite that percentage of spectrin+ and lamin A/C+ human fibers in both groups MRC were similar. Taken together, these data provide evidence that MRC generated in vitro represent a promising source of cells for improving regeneration of injured skeletal muscles.